The Impact of China's Direct Investment in Countries along the Belt and Road Initiative - Luo, Jingzhou (Transactions on Economics, Business and Management Research, 2024)
This article discusses the impact of China's direct investment in the countries surrounding the route on the international political environment on the basis of the road and highway strategy. Research shows that China's massive investment projects in the road and highway sector have promoted economic cooperation and development in the region and have a significant impact on the global political environment. China's direct investment has led to changes in the political environment and economic conditions of the countries along the ROW, expanding the economic relationship between these countries and China and changing the regional balance of power to some extent. The economic and infrastructural development brought by investment activities has provided a better internationalization path in the international arena, challenged the traditional dominance of the US dollar, and promoted the development of a diversified financial system. China's capital is changing China's international political environment A Western-oriented and different climate not only affects foreign relations, but also poses new demands and challenges for global governance. The final section emphasizes that China's road strategy is to build a new international political and economic order through direct investment. This process brings opportunities and challenges and requires all parties to respond to the emerging political and economic changes.